Evaluation of the band alignment and valence plasmonic features of a DIBS grown Ga-doped Mg0.05Zn0.95O/CIGSe heterojunction by photoelectron spectroscopy. (5th November 2015) - Awasthi, Vishnu; Pandey, Sushil Kumar; Kumar, Shailendra; Mukherjee, C; Gupta, Mukul; Mukherjee, Shaibal
Abstract: The bandgap alignment of a Ga-doped MgZnO (GMZO)/CIGSe heterojunction exposed to short duration Ar + ion beam sputtering has been investigated by ultraviolet photoelectron spectroscopy measurement. The offset values at the valence and conduction band of the GMZO/CIGSe hetrojunction are calculated to be 2.69 and −0.63 eV, respectively. Moreover, the valence band onsets of GMZO and CIGSe thin films before and after few minutes Ar + ion sputtering have been investigated. The presented study demonstrates the photoelectron-induced generation of resonant valence bulk and surface plasmonic features of various metal and metal oxide nanoclusters embedded within a GMZO matrix. The presence of such nanoclusters is proven to be beneficial in realizing cost-effective, ultra-thin, and high-performance photovoltaics based on the heterojunction.